2005
DOI: 10.1139/y05-045
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous prolactin modulated the calcium absorption in the jejunum of suckling rats

Abstract: Prolactin has been reported to stimulate intestinal calcium absorption in young and mature, but not aging rats. The present study was performed on suckling rats to elucidate the actions of endogenous prolactin on calcium absorption in various intestinal segments. Before measuring the calcium fluxes, 9-day-old rats were administered for 7 days with 0.9% NaCl, s.c. (control), 3 mg/kg bromocriptine, i.p., twice daily to abolish secretion of endogenous prolactin, or bromocriptine plus exogenous 2.5 mg/kg prolactin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 57 publications
(90 reference statements)
0
14
0
Order By: Relevance
“…Besides being an important regulator of intestinal calcium transport during pregnancy and lactation, prolactin also regulates calcium absorption in mammals during the neonatal period (Amnattanakul et al 2005). In suckling rats, sources of plasma prolactin are both endogenous of pituitary origin and exogenous of milk origin (approx.…”
Section: Prolactin As a Calciotropic Hormone In Neonatal Animalsmentioning
confidence: 99%
“…Besides being an important regulator of intestinal calcium transport during pregnancy and lactation, prolactin also regulates calcium absorption in mammals during the neonatal period (Amnattanakul et al 2005). In suckling rats, sources of plasma prolactin are both endogenous of pituitary origin and exogenous of milk origin (approx.…”
Section: Prolactin As a Calciotropic Hormone In Neonatal Animalsmentioning
confidence: 99%
“…Under conditions where only exogenous prolactin was present, net calcium absorption from the duodenum was absent. 55 This study illustrates the potential for endogenous and exogenous prolactin to confer different effects on intestinal calcium absorption. In adult mice and in human cell culture models, endogenous prolactin appears to increase calcium flux through an L-type calcium channel, presumably Ca v 1.3.…”
Section: Potential Mediators Of Changes In Intestinal Calcium Absorptmentioning
confidence: 80%
“…The jejunum appeared to be the segment of greatest net absorption which increased when luminal sodium decreased, independent of mannitol flux. 55 Thus, limited evidence supports transcellular calcium absorption from the distal small intestine prior to weaning. This is in contrast to net secretion from the jejunum and net absorption in the cecum in adult rodents.…”
Section: Changes In Intestinal Calcium Absorption During Postnatal Dementioning
confidence: 99%
“…By regulating calcium mobilization in these target organs during pregnancy and lactation, the high physiological PRL of 75-300 ng/ ml increases calcium availability for fetal growth and milk production [4]. Moreover, the basal PRL level of 7-10 ng/ ml was required for the maintenance of normal bone turnover and duodenal calcium absorption in rats [5,6].It has been shown that PRL acted directly on the intestinal absorptive cells to enhance calcium absorption [3]. In bone, osteoblasts but not osteoclasts strongly expressed functional PRL receptors (PRLR), indicating that bone was also a target of PRL [7].…”
mentioning
confidence: 99%
“…By regulating calcium mobilization in these target organs during pregnancy and lactation, the high physiological PRL of 75-300 ng/ ml increases calcium availability for fetal growth and milk production [4]. Moreover, the basal PRL level of 7-10 ng/ ml was required for the maintenance of normal bone turnover and duodenal calcium absorption in rats [5,6].…”
mentioning
confidence: 99%